A budget allocation model for domestic airport network protection. (August 2022) - Yan, Xihong; Ren, Xiaorong; Nie, Xiaofeng
Abstract: In order to protect a domestic airport network from terrorist attacks, we investigate how to allocate a limited amount of budget into airports with different characteristics. We propose a minimax optimization model, where the Transportation Security Administration decides the budget allocation of each airport in the upper level, while the terrorist group chooses which flights to attack in the lower level. The objective of the terrorist group is to maximize the expected damage and the objective of the Transportation Security Administration is to minimize the corresponding maximum damage. We adopt a generalized cutting-plane algorithm to solve the proposed bilevel optimization problem. Moreover, we provide an illustrative example, and present some detailed sensitivity analysis and comparison results. Highlights: Domestic airport network protection from terrorist attacks A bilevel optimization model to determine airport budget allocation decisions Managerial insights through a detailed computational study